Joint state estimation with integrated sensing and communications for UAV enabled 6G systems. Issue 2 (16th January 2023) - Zhao, Jianwei; Jia, Weimin; Zhang, Fenggan; He, Fang; Jin, Wei; Jiang, Nan
Abstract: Integrated sensing and communications (ISAC) is a key technique for UAV enabled 6G communications. In this paper, the joint state estimation problem for UAV aided 6G communications is considered. Firstly, the characteristics of the spatial channel is explored by considering the Jittering effects. Meanwhile, the channel characteristics of the spatial channel is analyzed. Then, a joint state estimation method is proposed by utilizing the ISAC technique, where the UAV attitude, the communication, and the control are jointly designed to benefit the system performance. Finally, various simulation results are provided to verify the performance of the proposed method. Abstract : Integrated sensing and communications (ISAC) is a key technique for 6G UAV communications. In this paper, we propose an efficient channel estimation method by utilizing the ISAC technique, where the UAV attitude sensing, the communication, and the control are jointly considered to benefit the system performance.